Recent research and development activities on space robotics and AI. (17th November 2021) - Doyle, Richard; Kubota, Takashi; Picard, Martin; Sommer, Bernd; Ueno, Hiroshi; Visentin, Gianfranco; Volpe, Richard
Abstract : Deep space exploration missions have received a lot of attention in the world, such as the moon, Mars, asteroids for scientific observation and human activities. Recently, not only space agencies but also industries or universities have earnestly studied and developed lunar or planetary robots for lunar or planetary exploration. International cooperative missions are also under discussion including human lunar exploration. Space robotics including Al is a key technology for planetary exploration as well as orbital service. Future space programs require space AI and robotics technology to construct, repair and maintain satellites and space structures in orbit. This paper introduces recent space missions and surveys hot topics on new research activities and developed technology for the near future missions. GRAPHICAL ABSTRACT: UF0001